(untitled) (Veterinary Science, 2017)
Contamination of urban environments with dog feces implies a problem for public and animal health. The objective was to determine the presence of zoonotic nematode in the public spaces of the area of the Brown Health Center (General Pico, La Pampa). Samples of feces and ground in public spaces were collected. Parasitological analysis´ were made. Results are presented in the samples taken in 2013 and 2014. In May 2013, 169 samples of feces were collected, 85 of them proved positive (50,3%) and 33 samples (19,5%) multi-parasites. In September, 198 samples were taken; 104 proved positive (52,5%) and 37 (18,6%) multi-parasite. In May 2014, 177 feces samples were collected, 70 (39,5%) proved positive and 34 (19,2%) multi-parasite. In October 241 were taken; 139 proved positive (57,7%) and 90 (37,3%) multiparasitadas. Predominant species in the study period were Ancylostoma sp. followed by Trichuris sp. In May 2013, 105 samples were taken, 40 (3,1 %) proved positive. In September, 45 samples were collected, 48 (52, 2%) proved positive. In May 2014, 92 ground samples were taken, 48 (52,2%) proved positive. In October were collected 115, 49 (42,6%). proved positive. The main parasite found was Ancylostoma sp. It can be concluded that public spaces, given the parasite amount found, represent a threat to public health, especially for children. Due to their ground interaction, playing habits and their behavior, they are the most vulnerable population to parasites. Implementation of information, communication and education strategies is needed for health insurance from an inter-disciplinary work perspective